SOME GRÜSS TYPE INTEGRAL - Aglić Aljinović, Andrea; Hoxha, Razim; Pečarić, Josip (Matematichki Bilten, 2005)
Few different versions of Grüss type inequalities are given, using the Euler identity, Fink identity and Anastassiou identity.